ChemInform Abstract: Synthesis and Photoluminescence Properties of Microcrystalline Sr2ZnWO6:RE3+ (RE: Eu, Dy, Sm and Pr) Phosphors. Issue 48 (2nd December 2014) - Dabre, K. V.; Park, K.; Dhoble, S. J.
Abstract Microcrystalline Sr2ZnWO6:Ln3+ (Ln: Eu, Dy, Sm, Pr) phosphors are prepared by solid state reaction of stoichiometric mixtures of SrCO3, ZnO, H2WO4, and Ln2O3 in air (1250 °C, 4 h).